Framing Transformation in Digital Political Communication: An Analysis of the Role of Political Influencer Denny Siregar on Social Media - Henry Sianipar; Pritha Ayodya; Andreas Sainyakit; Miftahol Anwar; Bagus Sudarmanto (INTERACTION: Jurnal Pendidikan Bahasa, 2025)
This study analyzes the framing transformation carried out by Denny Siregar as a political influencer on Indonesian social media during the period of 2014–2024. Using a qualitative approach with a constructivist paradigm and Robert Entman's framing analysis model, this research explores how Denny Siregar went through three significant transformation phases: the Ahok supporter phase (2014–2017), the Jokowi supporter phase (2014–2022), and the Jokowi critic phase (2022–2024). Data were collected through social media content analysis on Facebook, Twitter, Instagram, and YouTube, as well as secondary document analysis. The findings show that the framing transformation was influenced by political, economic, social media technology factors, and audience dynamics. In the Ahok supporter phase, the framing focused on bureaucratic reform and anti-corruption narratives using good personification strategies and moral polarization. The Jokowi supporter phase featured narratives of infrastructure development and counter-framing against opposition using selective data. The Jokowi critic phase employed betrayal narratives and historical reframing with value consistency positioning. This transformation impacted follower composition changes of up to 30% and a decline in engagement of up to 40%, while increasing discussion polarization. This research contributes to the development of framing theory by adding temporal and dynamic dimensions in social media contexts and offers practical insights into digital political communication strategies and their implications for Indonesian democracy.